The Qur'an Translation A guide and Mecy - Ali, Abdullah Yusuf (New York Tahrike Tarsile Qur'an, Inc., 2011)
The Koran, the holy scripture of Islam, is the record of Muhammad's oral teaching delivered between the years immediately preceding the Hegira in AD 622 and the Prophet's death in AD 632. Abdullah Yusuf Ali's translation of the Qur'an was first publishe
Keywords: Qurʼan. Muslims -- Sacred books. Muslims